The effectiveness of an Internet-based nutrition and fitness education program for senior military officers - Sigrist, Lori D., author; Anderson, Jennifer, advisor; DeVoe, Dale, committee member; Kennedy, Cathy, committee member; Auld, Garry, committee member (Colorado State University. Libraries, 2004)
A six-month Internet-based nutrition and fitness education program, entitled Taking Command of Your Health, to improve diet and fitness behaviors and physiological measures in a group of senior military officers enrolled in the Distance Education course at the U.S. Army War College. The intervention was based on the Transtheoretical Model (TTM) for behavior change and was delivered via the Internet. A needs assessment survey assessed senior military officers' health concerns, educational preferences for nutrition and health topics, eating habits, and motivators and barriers for eating healthfully and exercising regularly. Survey results determined the content of the intervention. Participants were randomly assigned to either a control group that did not have access to the website intervention or to the treatment group that had access to the program. The program was designed in a monthly newsletter format which combined nutrition and fitness information. Staging algorithm surveys determined stage of change for diet and exercise for participants each month. Participants were provided with stage-matched education based on the diet algorithm and all participants received identical fitness information regardless of stage for exercise. To evaluate the program, treatment participants completed exit surveys at the end of the intervention. Results of the study indicate that an intervention based on the TTM did not result in statistically significant improvement in behavioral and physiological measures between treatment and control groups. The program was effective in significantly progressing treatment participants through the stages for diet behavior, but not for exercise behavior. Unfortunately, dietary behavior change was not maintained as participants regressed to earlier stages after the intervention. In the exit survey, participants reported that they liked receiving health information over the Internet and they would recommend a similar program to others in the military. Future research on the implementation of a theory-based intervention should focus on an individual's cognitive and behavioral processes that determine one's success and failure with behavior change, factors that determine participation and regular usage of a website program, and the impact of program duration and content on other military populations.
Keywords: Nutrition; Physical fitness; Internet in education; Behavior modification